Convergence of Artificial Intelligence, Emotional Intelligence, Neural Network and Evolutionary Computing - Kumar, Neeraj; Singla, Ayush (IJRDO -Journal of Computer Science Engineering, 2015)
This paper presents a new perspective of Artificial Intelligence (AI). Although, number ofattempts has been made to make an artifact intelligent, including evolution theory, neuralnetwork etc and a number of problems have been solved using these concepts but each of thistheory covers only some aspect of human intelligence. Still there is a large gap betweenartificial intelligence agent and human being. Instrumental convergence is the hypotheticaltendency for most sufficiently intelligent agents to pursue certain instrumental goals such asself-preservation and resource acquisition.Instrumental convergence suggests that an intelligent agent with apparently harmless goalscan act in surprisingly harmful ways. For example, a computer with the sole goal of solvingthe Riemann hypothesis could attempt to turn the entire Earth into computronium in aneffort to increase its computing power so that it can succeed in its calculations.